(3α)-3-(tiglinoyloxy)-ent-kaur-16-en-19-oic acid, isolated from Wedelia trilobata L., exerts an anti-inflammatory effect via the modulation of NF-κB, MAPK and mTOR pathway and autophagy in LPS-stimulated macrophages. (June 2021) - Xu, Jingwen; Wang, Zhe; Sun, Lianlian; Wang, Yi; Wang, Yihai; He, Xiangjiu
Abstract: (3α)-3-(tiglinoyloxy)- ent -kaur-16-en-19-oic acid (WT-26) is an ent -kaurane dieterpenoid extracted from Wedelia trilobata L., a widely cultivated ornamental plant with several scientific reports supporting its anti-inflammatory activity. WT-26 has better anti-inflammatory activity than its analog Kaurenoic acid ( ent -kaur-16-en-19-oic acid). Nevertheless, the participation of WT-26 in the main signaling pathway associated with inflammation is lack of study. We aimed to study the anti-inflammatory effect of WT-26 and related signaling cascade in lipopolysaccharide (LPS)-stimulated macrophages. Here, we showed that WT-26 suppressed nitric oxide (NO) and prostaglandin E2 (PGE2 ) production in LPS-stimulated macrophages by downregulating the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in mRNA and protein level. WT-26 down-regulated tumor necrosis factor α (TNF-α), interleukin-6 (IL-6) and IL-1β production as well. Moreover, WT-26 inhibited the activation of nuclear factor-κB (NF-κB) p65 and its upstream signaling. WT-26 also reduced phosphorylation of mitogen-activated protein kinases (MAPKs) and mTOR. Besides, WT-26 decreased the overproduction of reactive oxygen species (ROS) and protected the mitochondrial integrity in stimulated macrophages. Our study also demonstrated that the autophagy induced by LPS was attenuated by WT-26. Collectively, our data indicated that WT-26 has the potential to be developed as a novel therapeutic agent for inflammatory-related diseases. Graphical abstract: Unlabelled Image Highlights: WT-26 showed anti-inflammatory effect in LPS-stimulated macrophages. WT-26 reduced iNOS and COX-2 expression, thereby suppressing the release of NO and PGE2. WT-26 suppressed the production of proinflammatory cytokine. Anti-inflammatory action was contributed to the inhibition of NF-κB, MAPK and mTOR signaling pathways. LPS-stimulated macrophages autophagy was down-regulated by WT-26.